1995
DOI: 10.1164/ajrccm.152.5.7582304
|View full text |Cite
|
Sign up to set email alerts
|

Exertional oxygen of limited benefit in patients with chronic obstructive pulmonary disease and mild hypoxemia.

Abstract: It is unclear whether short-term benefits from supplemental oxygen translate into improved quality of life in patients with severe COPD. In a 12 wk double-blind randomized crossover study, we assessed the effects of supplemental air and oxygen on exercise performance (step tests and 6 min walking distance [6MWD]) initially and after two 6 wk periods at home using exertional cylinder air or oxygen. We measured quality of life at baseline and after the two 6 wk domiciliary periods. The 26 patients (24 males) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
1
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 11 publications
1
111
1
3
Order By: Relevance
“…Some studies have found that, in patients who have only mild or nocturnal hypoxemia, oxygen therapy does not improve survival, 3,15 quality of life, 16 or activities of daily living. 17 By contrast, Eaton et al, who studied patients with COPD and exercise desaturation, found improved quality of life in their patients. 18 Fujimoto et al, who studied 75 patients with mild to severe COPD and mild hypoxemia, found that their desaturator patients walked farther in the 6-min walk test and had improved pulmonary pressure after administration of oxygen during exercise.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have found that, in patients who have only mild or nocturnal hypoxemia, oxygen therapy does not improve survival, 3,15 quality of life, 16 or activities of daily living. 17 By contrast, Eaton et al, who studied patients with COPD and exercise desaturation, found improved quality of life in their patients. 18 Fujimoto et al, who studied 75 patients with mild to severe COPD and mild hypoxemia, found that their desaturator patients walked farther in the 6-min walk test and had improved pulmonary pressure after administration of oxygen during exercise.…”
Section: Discussionmentioning
confidence: 89%
“…Oxygen therapy during exercise in patients normoxaemic at rest improves exercise endurance and dyspnoea [45][46][47][48], but may not have a direct enduring effect on exercise capacity. Despite previous studies of COPD patients trained while using supplemental oxygen failing to demonstrate benefits [49][50][51], supplemental oxygen during exercise training may enable individuals with COPD to tolerate higher levels of exercise activity with fewer exertional symptoms, ultimately improving their QoL, although larger studies are required in order to establish its effect on functional outcomes [52]. A randomised study failed to find an advantage in QoL of ambulatory oxygen over placebo in COPD patients who did not meet the criteria for mortality reduction with LTOT, thus not supporting the general off-label application of this treatment in patients not meeting recognised criteria for LTOT [53].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 98%
“…51 In an additional crossover randomized trial comparing portable oxygen versus air in 9 patients with a resting P aO 2 Ͻ 60 mm Hg, no differences in 6-min walk distances were found. 52 In a single blind trial in 20 patients, no significant differences in 6-min walk distance were found after 8 weeks of treadmill exercise training using either supplemental oxygen or compressed air.…”
Section: Exercisementioning
confidence: 93%